Development of a self-efficacy scale for preschool teachers on science teaching: Validity and reliability study - Kuş Gürbey, Sümeyya; Metin, Mustafa (Southeast Asia Early Childhood Journal, 2022)
The study was carried out in order to develop a valid and reliable scale aimed at determining the self-efficacy of preschool teachers regarding science teaching. In the study, survey method was used within the scope of quantitative research approach. The sample of the study consists of 612 teachers who are actively working in preschool institutions in the 2020-2021 academic year. In the study, a self-efficiency scale consisting of 52 items was used as a data collection tool. In order to ensure the validity of the scale, the content, face and structure validity were examined. Expert opinions were obtained for the content and face validity, and exploratory and confirmatory factor analysis were applied for the structure validity. As a result of expert opinions and exploratory factor analysis, four items were excluded from the scale and the scale consisting of two factors was confirmed by confirmatory factor analysis. As a result of confirmatory factor analysis, RMSEA value was found to be 0.058, GFI value was found to be 087, CFI value was found to be 0.91 and IFI value was found to be 0.91. In order to determine the reliability of the scale, Cronbach Alpha coefficient was calculated. As a result of the reliability analysis, the Cronbach alpha reliability coefficient of the scale was calculated as 0.97. As a result of the study, a valid and reliable 48-item scale consisting of a two-factor structure was developed to determine the self-efficacy of preschool teachers regarding science teaching.